A new species of Neomintho Brauer & Bergenstamm and provisional reclassification of the tribe Euthelairini (Tachinidae, Exoristinae) - O’hara, James E. (Zootaxa, 2026)
The Euthelairini are a tribe of New World Tachinidae (Diptera) with fewer than 30 described species and dozens of undescribed species. Most species are Neotropical and range from Mexico to Brazil, with only two described species in the Nearctic Region. One new species, Neomintho beckersi sp. nov., is described from Florida (United States) and Cayman Islands (Caribbean Sea). Several of the paratypes were reared from the katydid Neoconocephalus triops (L.) (Orthoptera: Tettigoniidae) by the researcher for whom the species is named, and this is the first host record for the Euthelairini. The tribal concept is well established but the number of genera has varied from one (Neomintho B. & B.) to 12 in recent decades. The tribe is reexamined on the basis of morphology and DNA barcoding to provide a basis for the generic assignments of the three Nearctic species. Results indicate that these species are each more closely related to other species in the Neotropical Region than to each other, and only the new species N. beckersi belongs to Neomintho sensu stricto. The classification of the Euthelairini is reviewed and provisionally revised, with seven genera and 27 described species recognized. The following taxonomic changes are proposed to the existing classification: Eupelecotheca Townsend, 1919 (including synonym Pantagathus Reinhard, 1935) is removed from synonymy with Neomintho Brauer & Bergenstamm, 1891 and recognized as a valid genus, status revived; synonymized with Neomintho are genus-group names Euthelaira Townsend, 1912, syn. nov., Iteuthelaira Townsend, 1927, syn. nov. and Neominthoidea Thompson, 1968, syn. nov.; new or revived combinations are proposed as Eupelecotheca celer Townsend, 1919, comb. revived, Neomintho chaetosa (Townsend, 1929), comb. nov., Neomintho esuriens (Fabricius, 1805), comb. nov., Neomintho inambarica (Townsend, 1912), comb. nov., Neomintho rufilabris (Wulp, 1890), comb. nov., Neomintho trinidadensis (Thompson, 1968), comb. nov. and Pelecotheca curulis (Reinhard, 1943), comb. revived. As First Reviser, the species name “flavipes” is selected as the correct original spelling in the combination Pelecotheca flavipes Thompson, 1968 and “flavipalpis” becomes an incorrect original spelling. The distribution of Neomintho macilenta (Wiedemann, 1830) is revised to Brazil only (previously misidentified from Trinidad). The monotypic genus Hypohoughia Townsend, 1927 is removed from the Euthelairini and placed in the Voriini (Dexiinae) based on study of the holotype of type species H. reclinata Townsend, 1927 by Rodrigo de Vilhena Perez Dios. A revised checklist of the genera and species of Euthelairini is provided.